Strategi Pemasaran Bank Syariah Indonesia Terhadap Generasi Millenial dan Gen Z: Pendekatan Marketing Mix Persfektif Lovelock dalam Meningkatkan Loyalitas Nasabah Persfektif UU Perbankan Syari’ah - Nia Puspita Hapsari; Liza Nora (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
The research aims to analyze the marketing strategy of Islamic banking services implemented by (BSI) to attract, and retain millennial and Gen Z customers a midst increasingly tight competition in the Islamic banking industry. Applying the services marketing mix approach according to Love lock (7P: Product, Price, Place, Promotion, People, Process, Physical Evidence), the study examines the effectiveness of BSI’s marketing strategy based on the perceptions, and satisfaction of Millennial, and Gen Z customers. The approach used is qualitative, with literature studies, digital media observation, and thematic analysis of BSI’s marketing campaign. The results show that BSI implements a digitization approach, modernly packaged Sharia values, and storytelling based on social benefits to attract the younger generation. The study is reviewed from the perspective of Law/No.21/2008” Sharia Banks emphasize the principles of fairness, transparency, and Sharia values in banking services. The findings provide strategic implications for BSI in formulating more segmented marketing policies based on the needs of the younger generation in line with the also provide strategic insights for Sharia banks in managing the market segmentation of Millenials and Gen Z sustainably.